Symptoms and Quality of Life of People Living with HIV Infection in Puerto Rico - Rivero-Méndez, Marta; Portillo, Carmen; Solís Báez, Solymar S.; Wantland, Dean; Holzemer, William L. (Puerto Rico Health Sciences Journal, 2009)
Background: People living with HIV infection are confronted with physical and psychological symptoms that impact their quality of life. This study explored the symptom experience of people living with HIV infection in Puerto Rico and its correlation with quality of life. Methods: A cross-sectional descriptive design was used to survey 44 men, women, and transgender people living with HIV infection. Measures included a demographic questionnaire, sign and symptom checklist, and a quality of life instrument. Results: The sample was 50% male with a mean age of 42.1 years; the participants had been living with HIV infection an average for 9.8 years. The top five symptoms reported by the sample included: muscle aches (81.8%), depression (77.2%), weakness (70.5%), fear/worries (70.5), and difficulty concentrating (65.9%). Symptom frequency was significantly related to four dimensions of quality of life: overall function (r=-0.58), life satisfaction (r=-0.59), health worries (r=0.32) and HIV medication worries (r=0.59). The symptom experience was not related to financial worries, disclosure worries, or sexual functioning. Individuals who reported taking HIV medications reported significantly fewer symptoms than those not taking HIV medications (t=3.061, df=42, p < 0.01). Conclusions: These results suggest that people living with HIV infection in Puerto Rico experience a wide array of physical and psychological symptoms and that these symptoms have a correlation with their perceived quality of life. Better management of symptoms may have an impact on perceived quality of life for people living with HIV infection.